Intestinal DHA-PA-PG axis promotes digestive organ expansion by mediating usage of maternally deposited yolk lipids - Zhengfang Chen; Mudan He; Houpeng Wang; Xuehui Li; Ruirui Qin; Ding Ye; Xue Zhai; Junwen Zhu; Quanqing Zhang; Peng Hu; Guanghou Shui; Yonghua Sun (Nature Communications, 2024)
Abstract Although the metabolism of yolk lipids such as docosahexaenoic acid (DHA) is pivotal for embryonic development, the underlying mechanism remains elusive. Here we find that the zebrafish hydroxysteroid (17-β) dehydrogenase 12a (hsd17b12a), which encodes an intestinal epithelial-specific enzyme, is essential for the biosynthesis of long-chain polyunsaturated fatty acids in primitive intestine of larval fish. The deficiency of hsd17b12a leads to severe developmental defects in the primitive intestine and exocrine pancreas. Mechanistically, hsd17b12a deficiency interrupts DHA synthesis from essential fatty acids derived from yolk-deposited triglycerides, and consequently disrupts the intestinal DHA-phosphatidic acid (PA)-phosphatidylglycerol (PG) axis. This ultimately results in developmental defects of digestive organs, primarily driven by ferroptosis. Our findings indicate that the DHA-PA-PG axis in the primitive intestine facilitates the uptake of yolk lipids and promotes the expansion of digestive organs, thereby uncovering a mechanism through which DHA regulates embryonic development.